Evaluation of the Growth of the Bursa of Fabricius in Broilers Reared under Different Light Photoperiods - Nuthalapati, Nikhil; Olanrewaju, Hammed A.; Branton, Scott L.; Pharr, Gregory T. (International Journal of Poultry Science, 2017)
Background and Objective: Previous studies have investigated the interaction of different light sources and light intensity. Studies are lacking concerning the effect of different light sources and photoperiods on broiler growth and health. The results reported here are a part of a larger study to evaluate the interaction of different light sources with different photoperiods on the growth of the bursa of fabricius. Materials and Methods: Twelve treatments were designed as a 3×4 factorial arrangement of 4 light sources, incandescent (ICD, control), compact fluorescent light (CFL), light emitting diode (LED) and poultry specific filtered LED (PSF-LED) with 3 different photo periods (short, regular and long). A total of 4 trials were conducted. For each trial a total of 720 broiler chickens were reared under the various light treatments from 8-43 days of age. At 43 days of age, 2 males and 2 females from each treatment group were weighed and then euthanatized for dissection to collect the bursa. The bursas were weighed and the bursa-to-body ratio calculated. Results: The interaction of light source, photoperiod and sex did not have a statistically significant effect on the bursa-to-body weight ratios. Conclusion: The light sources investigated did not have a negative effect on broiler health.